Calibrating bulk and amino acid δ13C and δ15N isotope ratios between bivalve soft tissue and shell for paleoecological reconstructions - Vokhshoori, Natasha L.; Tipple, Brett J.; Teague, Laurel; Bailess, Alexander; McCarthy, Matthew D. (Palaeogeography, palaeoclimatology, palaeoecology, 2022)
Ecological isotope proxies measured in ancient bivalve shell matrix protein have great promise for paleoecological reconstruction. Compound-specific isotopes of amino acids (CSI-AA) may be an ideal tool for developing paleoecological proxies, as initial work has indicated that CSI-AA is less subject to alteration under geologic conditions relative to bulk isotope values. While CSI-AA proxies have been applied in modern bivalve soft tissues and a few shell studies, they have yet to be systematically investigated in shell matrix protein. Here, we measured stable isotope values of carbon (δ13C) and nitrogen (δ15N) in both bulk and individual amino acids (AA), comparing soft tissue and shell organic fractions to test the fidelity of a suite of ecological isotope proxies in shell. We sampled three ubiquitous bivalve species in four seasons for one year from two common coastal environments: littoral rocky intertidal and estuarine delta ecosystems. Particulate organic matter (POM) was simultaneously collected to investigate relationships between tissue types and local POM isotope signatures. The ecological proxies tested include trophic niche breadth from bulk isotopes, and baseline δ13C and δ15N values, resource contribution, and trophic level from CSI-AA data. We found niche breadth corresponded well between tissue types, but that bulk isotope values were significantly higher in shell compared to soft tissue. In the CSI-AA record, there were no differences in baseline δ13C and δ15N proxies between tissue types. While no consistent seasonal trends were observed in the δ13C record, summer bulk and baseline δ15N values were lowest in both ecosystems in both tissues. Food resource contribution estimates from shell also closely matched soft tissue, however trophic level estimates were consistently higher in shell, attributed to a systematic offset in Glutamic acid δ15N values. We therefore propose here a new mollusk-specific trophic discrimination factor, and corresponding shell isotope enrichment factor to correct for isotopic routing, both required for accurate paleoecological reconstructions. •First study to directly examine CSI-AA proxies in bivalve shell matrix protein.•Ecological CSI-AA proxies in shell closely match those in soft tissue.•Baseline δ13C and δ15N marine source values can be reconstructed in shell protein.•CSI-AA trophic level in bivalve tissues must be corrected using two constants.•CSI-AA proxies in bivalve shell is a new bioarchive for palaeo reconstructions.